A sustainable cheese packaging survey involving scientific papers and patents. (15th April 2021) - Spreafico, Christian; Russo, Davide
Abstract: The aim of this survey is to provide an overview about what efforts have been spent during the years by academia and industry make cheese packaging more sustainable. The analysis followed is based on a structured methodology that has general validity. A large pool of scientific papers (403) and patents (2272) was analysed and classified by identifying the exploited eco-strategies, the materials, the types of protected cheeses and by intersecting them to obtain more detailed classifications. The review is accompanied by graphs and tables to explain trends and to select the most representative papers or patents. Overall, the most followed strategies are improving cheese shelf life with active/vacuum or modified atmosphere packaging and using biodegradable packaging. The preferred materials are bioplastic with vegetal origin, followed by synthetic plastics. A great attention is paid to soft cheese and its requirements, such as the rapid perishability. Some discrepancies were found, mainly between the strategies covered by the papers and the patents and partly on the claimed materials. In particular, over the years, papers have become more interested in increasing cheese shelf life, especially by using active packaging, while patents remain strongly focused on biodegradable packaging. Finally, while not excluding biodegradability, it would seem that the development of cheese packaging could lean more towards active and smart (sensorized) ones in the future, even in industry. Graphical abstract: Image 1 Highlights: Survey of 403 scientific papers and 2272 patents about sustainable cheese packaging. Analysis and classification by eco-strategies, packaging materials, and types of contained cheese. Analysis of the identified mismatching between papers and patents about strategies and materials. Relevant topics are biodegradable packaging and increasing cheese shelf life through active packaging. Most used materials are bioplastic with vegetal origin and synthetic plastics.